CULTURE BASED POLITICAL MESSAGE CONSTRUCTION TO INCREASE VOTER PARTICIPATION - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the construction of culturally based political messages and their impact on increasing voter participation. Although voter participation in Indonesia is relatively high compared to the global average, challenges in maintaining consistent participation, especially among the younger generation, remain. Using the approachnarrative reviewThis study analyzed literature from the Scopus and Web of Science databases (2000-2025) with keywords such as